DIVERSITY OF FRESHWATER ZOOPLANKTON IN COLLIDAM RIVER NEAR NEELATHANALLUR - MOHANAMBAL, R.; RAJASEKARAN, R.; SARAVANAN, K.; UDHAYA, S. ABARNA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Zooplankton plays an important role in aquatic ecosystem. They link primary producers, phytoplankton with higher larger tropic level organisms. Many aquatic organism exhibit diurnal rhythms in their activities, although factors such as light, temperature, food, sex and size have been attributed as probable causes for such behavior of planktonic organisms. Zooplankton provides the necessary amount of protein required for the rapid growth and development of organs of fishes. The larvae of most fishes feed mostly on zooplankton. Growth and abundance of zooplankton varies with season and depth and depends upon meteorological and water properties. Temperature plays vital role in the vertical distribution of zooplankton. The work was conducted by the monthly changes in zooplankter recorded in coleroon river, situated near by Neelathanallur (Thanjavur district).